(untitled) - Corey, E. J (New York, 1995)
This three-part volume derives from a key theme of the book-the logic underlying the rational analysis of complex synthetic problems. Although the book deals almost exclusively with molecules of biological origin, which are ideal for developing the fundamental ideas of multistep synthetic design because of their architectural complexity and variety, the approach taken is fully applicable to other types of carbon-based structures
Tổng hợp hữu cơ,Tổng hợp hữu cơ
Keywords: Organic compounds,Các hợp chất hữu cơ; Synthesis,Tổng hợp